Analisis kepuasan kerja karyawan pada PT Aneka gas industry - Desiana Sagala; Hendra Nazmi (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2022)
ABSTRACT Aneka Gas Industri Tbk, Medan is one of the largest companies in Indonesia. As a large company, it is necessary to pay attention to, review and regulate human resource management and good support for the performance of its employees, so that it will have an impact on improving employee performance which can have a good influence on company profits. The data obtained by the authors were obtained through the results of questionnaires filled out by employees of PT Aneka Gas Industri Tbk, Medan. The level of employee job satisfaction is assessed based on 5 aspects, namely aspects of the work itself, aspects of salary/compensation, aspects of the presence or absence of career paths, aspects and support from colleagues, and aspects of superior leadership. The results showed that the percentage level of employee satisfaction with the work itself was 76%, the level of employee satisfaction with salary/compensation was 75%, the level of employee satisfaction with the career path was 70%, the level of employee satisfaction with colleagues was 85%, and the level of employee satisfaction with superiors is 76%. The percentage of feeling satisfied with the work of employees Medan is dominantly satisfied, which is 83.3%.